Population-Based Analysis of Firearm Injuries among Young Children in the United States, 2010–2015. Issue 5 (May 2019) - Cook, Alan; Hosmer, David; Glance, Laurent; Kalesan, Bindu; Weinberg, Jordan; Rogers, Amelia; Schultz, Cpt Susan; Gilligan, Cpt Timothy; Gross, Brian; Vernon, Tawnya; Ward, Jeanette; Osler, Turner; et al.
Firearm violence in the United States knows no age limit. This study compares the survival of children younger than five years to children and adolescents of age 5–19 years who presented to an ED for gunshot wounds (GSWs) in the United States to test the hypothesis of higher GSW mortality in very young children. A study of GSW patients aged 19 years and younger who survived to reach medical care was performed using the Nationwide ED Sample for 2010–2015. Hospital survival and incidence of fatal and nonfatal GSWs in the United States were the study outcomes. A multilevel logistic regression model estimated the strength of association among predictors of hospital mortality. The incidence of ED presentation for GSW is as high as 19 per 100, 000 population per year. Children younger than five years were 2.7 times as likely to die compared with older children (15.3% vs 5.6%). Children younger than one year had the highest hospital mortality, 33.1 per cent. The mortality from GSW is highest among the youngest children compared with older children. This information may help policy makers and the public better understand the impact of gun violence on the youngest and most vulnerable Americans.